An exploratory study of the costs of job insecurity in Nigeria (2010)
The vast majority of research on job insecurity has been conducted within Western Europe and North America. The purpose of the current research was to determine whether previously documented effects of job insecurity on attitudes, behaviors, and health-related outcomes would be replicated in a Nigerian sample of mill workers. Using survey data, results indicated that job insecurity was related to lower levels of coworker, work, and supervisor satisfaction; greater turnover intentions; and worse safety attitudes (knowledge and motivation), fewer safety compliance behaviors, and increased injuries. These results are discussed within the context of the Nigerian economy and culture